Central retinal artery occlusion following embolization in juvenile nasopharyngeal angiofibroma – A case report - Pantelić, Jelica; Karadžić, Jelena; Kovačević, Igor; Bulatović, Jelena (Vojnosanitetski pregled, 2020)
Introduction. Juvenile nasopharyngeal angiofibromas are highly vascular, locally aggressive lesions, that affect male adolescents. The surgery is the treatment of choice, although it shows a strong propensity to bleed during surgical removal. Preoperative embolization enables the surgical approach in a less bloody way and also a complete resection of the tumor. However, this procedure is not without complications. The most severe complication of this technique is a migration of an embolus into the intracranial circulation. Case report. We present a 9-year-old boy who lost vison on his left eye following preoperative embolisation of juvenile nasopharyngeal angiofibromas as a result of central retinal artery occlusion. A recent review of the literature reported only three previously documented cases of central retinal artery occlusion occurring after embolization for a nasopharyngeal angiofibroma. We want to point out the possibility of this rare but devastating complication and the importance of rapid and accurate diagnosis and treatment so that a visual outcome could be better when applying an early medical treatment. Conclusion. Described case of central retinal artery occlusion is a rare and unusual, iatrogenic vascular event, that could arise as a complication from embolisation of nasopharingeal tumors. However, physicians (ophthalmologists and ear-nose-throat surgeons) should be aware od this devastating complication, and the close evaluation of angiograms for detection of any vascular abnormality before and during the embolization is crucial.